Geodemographics of Travel E-shoppers: An Empirical Analysis of UK Consumers - Kamarulzaman, Y. (EuroJournals, 2010)
Among all the industries, the travel industry has clearly benefited the most from the development of Internet technology. Obviously, the Internet has changed how people interact with travel agents, for example, the issuance of e-tickets for flights has replaced the ticketing counters of travel agents and airlines offices. This study aims to fill the gaps in the current understanding of the potential of expanding the online market for travel services in the United Kingdom through examining the geodemographic profile of online shoppers. This study involved analysing the customers' demographic and geographic data and their purchasing pattern. The results are consistent with past models and commercial databases that have been adopted by many companies in segmenting their market. The study offers suggestions for consideration by businesses and the government.